Towards an Improved Pathological Node Classification for Prognostic Stratification of Patients With Oral Cavity Squamous Cell Carcinoma: Results From a Nationwide Registry Study - Kang, Chung-Jan; Wen, Yu-Wen; Lee, Shu-Ru; Ng, Shu-Hang; Tsai, Chi-Ying; Lee, Li-Yu; Chu, Ying-Hsia; Lin, Chien-Yu; Fan, Kang-Hsing; Wang, Hung-Ming; Hsieh, Chia-Hsun; Yeh, Chih-Hua; et al. (Frontiers in Oncology, 2022)
Background: To assess the prognostic significance of different nodal parameters (i.e., number of pathologically positive nodes, log odds of positive lymph nodes, lymph node ratio [LNR], and extra-nodal extension [ENE]) in Taiwanese patients with oral cavity squamous cell carcinoma (OCSCC), and to devise an optimized pN classification system for survival prognostication of OCSCC. Methods: A total of 4287 Taiwanese patients with first primary OCSCC and nodal metastases were enrolled. Cox proportional hazards regression analysis with the spline method was applied to identify the optimal cut-off values for LNR, log odds of positive lymph nodes, and number of pathologically positive nodes. Results: On multivariable analysis, we identified a LNR ≥0.078/0.079, the presence of at least three pathologically positive nodes, and ENE as independent prognosticators for 5-year disease-specific survival (DSS) and overall survival (OS) rates. We therefore devised a four-point prognostic scoring system according to the presence or absence of each variable. Our patients had poorer survivals with higher scores accordingly, and their 5-year DSS rates and 5-year OS rates of 0−3 scores were 70%/62%/50%/36%, respectively (p<0.0001), and 61%/52%/40%25%, respectively (p<0.0001). For AJCC 2017 pN classification, our patients with pN3a disease showed better survival rates than those with pN2. The 5-year DSS and OS rates of our patients with pN1/pN2/pN3a/pN3b disease were 72%/60%/67%/43% (p<0.0001) and 63%/51%/67%/33%, respectively (p<0.0001). Conclusions: The three nodal parameters (i.e., a LNR ≥0.078/0.079, the presence of at least three pathologically positive nodes, and ENE) assessed in combination provided a better prognostic stratification than the traditional AJCC pN classification.